2018
DOI: 10.1177/2165143418811830
|View full text |Cite
|
Sign up to set email alerts
|

Postsecondary Education-Focused Transition Planning Experiences of English Learners With Disabilities

Abstract: Postsecondary education has become increasingly important as the gap in earnings between high school and college graduates continues to widen (Pew Research Center, 2014). Census Bureau data indicate that 88% college graduates and 77% of those with some college were employed, as compared with 69% of high school graduates (McFarland et al., 2017). Although postsecondary education outcomes have generally improved for students with disabilities as a whole, progress has not been consistent across disability, racial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…Parent expectations have also been linked to children’s academic achievement (Zhang et al, 2011); school engagement (Christenson & Carlson, 2005; Simons-Morton & Chen, 2009); student’s involvement and active participation in Individual Education Program (IEP)/transition planning meetings (Wagner et al, 2012); and college attendance, adjustment, and achievement (Agliata & Renk, 2008; Kim & Schneider, 2005). Other studies have investigated African American, Latino, and immigrant parent expectations for children’s academic achievement and adult outcomes (Aldous, 2006; Landmark et al, 2007; Trainor et al, 2019; Zhang et al, 2011). These studies have shown that parents in these ethnic groups hold high expectations that their children will pursue postsecondary education goals.…”
mentioning
confidence: 99%
“…Parent expectations have also been linked to children’s academic achievement (Zhang et al, 2011); school engagement (Christenson & Carlson, 2005; Simons-Morton & Chen, 2009); student’s involvement and active participation in Individual Education Program (IEP)/transition planning meetings (Wagner et al, 2012); and college attendance, adjustment, and achievement (Agliata & Renk, 2008; Kim & Schneider, 2005). Other studies have investigated African American, Latino, and immigrant parent expectations for children’s academic achievement and adult outcomes (Aldous, 2006; Landmark et al, 2007; Trainor et al, 2019; Zhang et al, 2011). These studies have shown that parents in these ethnic groups hold high expectations that their children will pursue postsecondary education goals.…”
mentioning
confidence: 99%
“…Other times family context and needs are not taken into account. Many families of English language learners with disabilities experience poverty, yet rarely receive information from schools during transition meetings about financial resources to alleviate the costs of postsecondary education and career development (Trainor, Newman, et al, 2019). In summary, poor transition programming, a lack of communication and access to information, and negative teacher attitudes have led to many families being pushed out of more formalized school-based transition planning (Hirano et al, 2018; Wilt & Morningstar, 2018).…”
mentioning
confidence: 99%
“…Some youth were still in high school, and among the high school completers, all were still in the early stages of employment, so outcomes may not have been fully realized. Future research should look at long-term impacts of services and supports on both education and employment outcomes (Trainor et al, 2019).…”
Section: Discussionmentioning
confidence: 99%